Al-Farabi cultural heritage in the national and world semiotic system: the postage stamp (Journal of Philosophy Culture and Political Science, 2025)
The article explores the artistic experience of depicting the outstanding thinker of the Arab-Muslim East, a native of Deshti-Kipchak Abu Nasir al-Farabi in the world and national culture, and in the modern design of the postage stamp.  The main value is to comprehensively investigate the history of al-Farabi's image creation in the world visual and semiotic tradition and compile their chronicle by considering stamps issued in different periods of time.The novelty and methodological value of the article comes from the assessment of the contribution of Kazakh and world scientists and designers to culture and art history. The authors use analytical, historical, semiotic and other methods of research.The practical value of her study is the development of the classification of visual images of the great scientist.The theoretical value of the study comes from the nature of the multifaceted personality of the Turkic genius. There is not yet, and has not been, a systematic study of this image in the history of art. Postage stamps and the visual images they generate are unique cultural objects, providing a great deal of insight into our contemporary culture. It is important to promote al-Farabi's cultural and historical heritage, to write workshops to train future designers and art historians; it is necessary to talk about the ever-increasing importance of al-Farabi as a scholar in world cultural history. The value of the research is justified by the fact that the philosopher is the common historical and cultural heritage of the Turkic and Arab-Iranian peoples, although he came from our Kazakh land: the Kazakh National University, the flagship of the country, bears his name. The study of the creation of al-Farabi's artistic image has a valuable educational, educational, cognitive and cultural value, both for the modernization of public consciousness, and for the spiritual revival of our science.Key words: al-Farabi, history and theory of design, postage stamp, cultural heritage.